Osmoregulators on in vitro encapsulation of potato ‘BRS Clara’ buds - Vargas, Daiane Peixoto; Coradin, Juliana Hey; Ferreira, Letícia Vanni; Dorneles, Athos Odin Severo; Valgas, Ricardo Alexandre; Pereira, Arione da Silva; Castro, Caroline Marques; Dutra, Leonardo Ferreira (Plant Cell Culture & Micropropagation - ISSN 1808-9909, 2020)
Synthetic or artificial seeds via encapsulated propagules could be used for in vitro regeneration and mass multiplication, for germplasm preservation and exchange of plant materials. An in vitro encapsulation of potato ‘BRS Clara’ buds efficient protocol was established. Lateral buds were immersed in a 4% sodium alginate matrix, dripped in CaCl2 for 20 minutes in different osmoregulatory agents: sucrose (8.72, 15.00, 21.28 and 30.00 g L-1) and mannitol (0.00, 11.63, 20.0, 28.37 and 40.0 g L-1). They were then held for 30 days at approximately 4°C and subsequently immersed in KNO3 for capsule decomplexing. Afterward, they were inoculated in MS medium with 3% sucrose and cultured in a growth room under irradiance of 43 μmol m-2 s-1, 16 hours-photoperiod and 25±2 °C temperature. Sucrose and mannitol at concentrations of 15 g L-1 and 20 g L-1, respectively, associated with the encapsulation matrix promoted 80% survival rate of ‘BRS Clara’ encapsulated buds. Keywords: Germplasm preservation, Sodium alginate, Solanum tuberosum, Tissue culture